THE COMBINED EFFECTS OF STRESS RATIO AND YIELD STRENGTH ON THE LEFM FATIGUE THRESHOLD CONDITION - Lal D.N. (My University, 2025)
Abstract— Long‐crack (LEFM) fatigue threshold, Δ,K0 values are predicted which include the commonly observed effects of stress ratio, R, and yield strength, σy. It is assumed that the yield strength effect on threshold is indirectly related to grain size and so is not an independent variable. Two intrinsic thresholds of a material are invoked to explain the observations of higher ΔK0 values and a higher R‐ratio sensitivity of ΔK0 in low strength materials compared to high strength materials. The paper shows that ΔK0 is almost independent of both yield strength and stress ratio at high values of the stress ratio. Quantitative relations are developed to estimate curves of (i) ΔK0 versus R and (ii) ΔK0 versus σy. These curves show good agreement with experimental data for steels and aluminium alloys. A method is presented that may be used as an alternative procedure for obtaining quick and conservative estimates of ΔK0 for design applications. Copyright © 1992, Wiley Blackwell. All rights reserved